Associations between mental wellbeing and fMRI neural bases underlying responses to positive emotion in a twin sample. Issue 4 (2nd March 2023) - Park, Haeme R.P.; Chilver, Miranda R.; Montalto, Arthur; Jamshidi, Javad; Schofield, Peter R.; Williams, Leanne M.; Gatt, Justine M.
Abstract: Background: Although mental wellbeing has been linked with positive health outcomes, including longevity and improved emotional and cognitive functioning, studies examining the underlying neural mechanisms of both subjective and psychological wellbeing have been sparse. We assessed whether both forms of wellbeing are associated with neural activity engaged during positive and negative emotion processing and the extent to which this association is driven by genetics or environment. Methods: We assessed mental wellbeing in 230 healthy adult monozygotic and dizygotic twins using a previously validated questionnaire (COMPAS-W) and undertook functional magnetic resonance imaging during a facial emotion viewing task. We used linear mixed models to analyse the association between COMPAS-W scores and emotion-elicited neural activation. Univariate twin modelling was used to evaluate heritability of each brain region. Multivariate twin modelling was used to compare twin pairs to assess the contributions of genetic and environmental factors to this association. Results: Higher levels of wellbeing were associated with greater neural activity in the dorsolateral prefrontal cortex, localised in the right inferior frontal gyrus (IFG), in response to positive emotional expressions of happiness. Univariate twin modelling showed activity in the IFG to have 20% heritability. Multivariate twin modelling suggested that the association between wellbeing and positive emotion-elicited neural activity was driven by common variance from unique environment ( r = 0.208) rather than shared genetics. Conclusions: Higher mental wellbeing may have a basis in greater engagement of prefrontal neural regions in response to positive emotion, and this association may be modifiable by unique life experiences.